Expression of circular RNAs during C2C12 myoblast differentiation and prediction of coding potential based on the number of open reading frames and N6-methyladenosine motifs - Chen, Rui (Cell Cycle, 2018)
The importance of circular RNAs (circRNAs) as regulators of muscle development and muscle-associated disorders is becoming increasingly apparent. To explore potential regulators of muscle differentiation, we determined the expression profiles of circRNAs of skeletal muscle C2C12 myoblasts and myotubes using microarray analysis. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed to explore circRNA functions. We also established competing endogenous RNA (ceRNA) networks using bioinformatics methods and predicted the coding potential of differentially expressed circRNAs. We found that 581 circRNAs were differentially regulated between C2C12 myoblasts and myotubes. Bioinformatics analysis suggested that the primary functions of the linear transcripts of the circRNAs were linked with organization of the cytoskeleton, calcium signaling, cell cycle, and metabolic pathways. ceRNA networks showed that the myogenic-specific genes myogenin, myocyte enhancer factor 2a, myosin heavy chain (Myh)-1, Myh7, and Myh7b could combine with 91 miRNAs and the top 30 upregulated circRNAs, forming 239 edges. According to the number of open reading frames and N(6)-methyladenosine motifs, we identified 224 circRNAs with coding potential, and performed GO and KEGG analyses based on the linear counterparts of 75 circRNAs. We determined that the 75 circRNAs were related to regulation of the actin cytoskeleton and metabolic pathways. We established expression profiles of circRNAs during C2C12 myoblast differentiation and predicted the function of differentially expressed circRNAs, which might be involved in skeletal muscle development. Our study offers new insight into the functions of circRNAs in skeletal muscle growth and development.